The Evaluation of PDDIKTI User Acceptance Using The Unified Theory of Acceptance and Use of Technology Approach - Ady Bakri , Asri; Rino Vanchapo, Antonius; Assery, Syeh; M. Usulu, Elvira; Juli, La (SEULANGA SYSTEM PUBLISHER, 2023)
The scope of this research is about a database application system called Feeder PDDIKTI, where the application can be used as a complete data storage medium by all universities in Indonesia, both university data, lecturer data, study program data, and student data. However, in its application there are still some weaknesses that are felt by users while using the system.The purpose of study is to determine how well-liked the program is by users and to find out what factors affect user acceptance of the application using the modified Unified Theory of Acceptance and Use of Technology (UTAUT) model, whose data testing is assisted by using IBM SPSS. Thus, of the seven hypotheses put forth by the researcher, five are accepted, including Performance Expectancy, Social Influence, and Perceived Credibility, which are all shown to have a significant positive impact on behavioral intention in user acceptance. Facilitating Conditions and Behavioral Intention also have a significant positive impact on use behavior in user acceptance, while Effort Expectancy and Anxiety are shown to have no significant influence.